Pernikahan Tunggal Wuwung dalam Pandangan Hukum Islam - Bagus Achmad Faishol (Institut Agama Islam Negeri (IAIN) Kediri, 2017)
Javanese society in particular at Karangsono’s Village look on tradition of tunggal wuwung marriage as jurisdictional which at abides (performed). There is another Javanese tradition besides prohbitions in tunggal wuwung marriage which is the day count terminological to Java custom before the marriage performing, since if that thing is unperformed, therefore, they believe that there will happen something bad luck. Islam has no prohibition on tunggal wuwung marriage but in the Islamic conjugal rights, it has been known base which so called the selection. This research based on the location of data source comprises field research category, and sighted from data character facets includes in qualitative researches, based on the data analysis included in descriptive research. Data collection utilizes observation, interview, and documentation. Data analysis was done from data reduction, data presentation, and conclusion. To test the data validity was done by prolongation attendance, triangulation, colleague’s analysis and informan’s clarification. This observational result can be concluded that 1). Opinions from the society of Karangsono’s village which has two perceptions: the majority society believes about the prohibitions in tunggal wuwung are based on the fact of bad luck incidents suffered by the doers of tunggal wuwung marriage who are not obedient on the custom’s prohibitions. Second perception is the incredulous with the marks sense of prohibitions in tunggal wuwung marriage because on a strength basic religion and beliefs of God that faith, alive and death are God’s authority. 2) Even the practice of tunggal wuwung is performed by Islamic marriage but constant breach custom, on reality the doers will suffer some badluck. 3) Tunggal wuwung marriage which strongly kept and trusted by the society of Karangsono’s Village is clearly in conflict with Islamic way because doesn not exsist in Al-quran and also Al Sunnah. However, in fact, to one of society it is at nature faced by the doer who suffers badluck of parent’s accidentut. Further, Islam teaches that all coming accidents are God’s will. Hence, it all just a test for every human being to hold firmly on syari ’ at Islam.